2008
DOI: 10.1002/ijc.23418
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia selects for androgen independent LNCaP cells with a more malignant geno‐ and phenotype

Abstract: Hypoxia confers resistance to common cancer therapies, however, it has also has been shown to result in genetic alterations which may allow a survival advantage and increase the tumorigenic properties of cancer cells. Additionally, it may exert a selection pressure, allowing expansion of tumor cells with a more aggressive phenotype. To further assess the role of hypoxia in malignant progression in prostate cancer we exposed human androgen dependent prostate cancer cells (LNCaP) to cycles of chronic hypoxia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 28 publications
7
61
0
Order By: Relevance
“…To our knowledge, however, a reduction in vascularity within non-tumour regions of the prostate over time has not been described previously. It may be that this factor is an important driver of disease progression, and this is supported by ex vivo findings of increased hypoxia in more aggressive tumour types [16]. A larger series using dynamic contrastenhanced MRI to compare modelled vascular parameters of perfusion and permeability in patients on active surveillance programmes would be useful.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, however, a reduction in vascularity within non-tumour regions of the prostate over time has not been described previously. It may be that this factor is an important driver of disease progression, and this is supported by ex vivo findings of increased hypoxia in more aggressive tumour types [16]. A larger series using dynamic contrastenhanced MRI to compare modelled vascular parameters of perfusion and permeability in patients on active surveillance programmes would be useful.…”
Section: Discussionmentioning
confidence: 94%
“…In one study, hypoxia only caused death of tumour cells when oxygen levels were ,0.01% (0.075 mmHg) for more than 24 h. 42 In our studies, a proportion of LNCaP tumour cells survived exposure in vitro to 48 h or longer of 0.1% oxygen. 43 More recently, we have shown that the median oxygen level of bicalutamide-treated LNCaP prostate xenografts remained below 0.1% oxygen for more than 10 days. 44 Overall, survival in this extreme stress will drive selection for malignant phenotypes that are governed by a Darwinian selection process.…”
Section: Pathological Hypoxiamentioning
confidence: 92%
“…62 Early studies have shown that hypoxia selected for cells with defects in apoptosis. 6 Further reports have confirmed that hypoxia can impose a selection pressure that allows clonal variant expansion in vitro 43,63,64 and in vivo. 55 Studies in our laboratory showed that mice bearing LNCaP xenografts exposed to bicalutamide-induced hypoxia had increased metastasis to the lungs; this correlated with an increase in Bcl2 and reduction in Bax.…”
Section: Variability In Tumour Oxygenationmentioning
confidence: 93%
“…Data from the author's laboratory provides a strong link between intratumor oxygen level and angiogenic responses [12]. Generally, intra-tumor oxygen play a major role in up regulation of pro-angioogenic factor such as VEGF-A -an endothelial cells' specific mitogen [13]. In fact, the transcriptional regulation of VEGF-A is mediated by hypoxia inducible factor 1 alpha (HIF-1α) [14].…”
Section: The Vasculaturementioning
confidence: 99%